Official Policies and Teachers’ Tendency to Act: Exploring the Discrepancies in Teachers’ Perceptions - Shapira – Lishchinsky, Orly; Gilat, Israel Zvi (Education Policy Analysis Archives, 2015)
The aim of the study is to investigate whether there are discrepancies between teachers’ perceptions of the ‘official policies’ and their ‘tendency to act,’ based on their ethical decision-making. A qualitative analysis of 60 Israeli teachers’ questionnaires consisting of critical ethical incidents revealed multifaceted ethical dilemmas nested in categories of ‘discrepancies between official policies and teachers’ tendency to act: ‘Harm (to people, property),’ ‘parental involvement/ interference’ and ‘academic process.’ The discrepancies noted between official policy and teachers’ tendency to act may encourage educational policy to design teachers’ training and professional development programs that include dealing with critical ethical incidents, through team-based simulations and formulating ethical guidelines based on their ethical decision-making process.